Accuracy of fit of digitally fabricated prototypes with different printers: A Comparative Study - Alhumaid, Naif. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Posthodontics.; Advisor: Panagiotis Papaspyridakos.; Committee: Khaled El Rafie, Jain Shruti, and Yukio Kudara.; Keyword: Dentistry.